Lost in translation: Cultural divides in communication skills teaching identified in the ICCH 2016 student symposium. Issue 11 (November 2017) - Schopper, Heather K.; Mohamed, Nasteha A.; Seegel, Max; Gorina, Kseniya; Silverman, Jonathan; Rosenbaum, Marcy
Highlights: Learners' voices are important in designing curriculum. Students face many challenges in learning effective communication skills. Transitions in medical education may lead to loss of communication skills. Support for communication skills teaching is still needed in multiple environments. Abstract: Objective: To provide a platform for learners' voices at an international conference on communication in healthcare. Methods: A group of medical students were invited to explore their experiences with communication skills learning at a symposium at the 2016 International Conference on Communication in Healthcare in Heidelberg, DE. Results: Students from the US, Denmark, Germany, and Russia discussed their experiences with communication skills curriculum at their institutions. We identified divides that have challenged our ability to develop and maintain strong communication skills: 1) valuation of communication skills vs. other topics, 2) curricular theory vs. practice, 3) evaluation vs. feedback, 4) preclinical vs. clinical learning, and 5) the medical student vs. practicing clinician role. Conclusion: The points of transition we identified on the road of communication skills teaching highlight opportunities to strengthen the educational experience for students. Without an effort to address these divides, however, our communication skills may be lost in translation. Practice implications: Students value communication skills teaching during their medical education and there are opportunities to translate this to countries that currently lack robust curricula and to the real-life post-graduate setting. Support is necessary from students, teachers, and administrators, and focus on translation of skills during role transitions is needed.